Manajemen Paduan Suara Consolatio Universitas Sumatera Utara - Octaviana Tobing (Universitas Negeri Medan, 2018)
This study aims to determine the management of the University of North Sumatra Consolatio Choir, regarding planning, implementation, and monitoring of evaluations that have been carried out. This study uses a qualitative descriptive analysis approach. Data collection is obtained through: interviews, observation and documentation studies. The research informants were the Chair of the Daily Management Board, Conductor, and Members of the USU Consolation Choir. Data analysis was performed using qualitative data analysis and with technical inductive analysis. Qualitative research is basically building theory, so in this study there is a new theory that is built namely